Truly Fluorescent Excitation‐Dependent Carbon Dots and Their Applications in Multicolor Cellular Imaging and Multidimensional Sensing. (21st October 2015) - Pan, Lulu; Sun, Shan; Zhang, Aidi; Jiang, Kai; Zhang, Ling; Dong, Chaoqing; Huang, Qing; Wu, Aiguo; Lin, Hengwei
Abstract : Truly fluorescent excitation‐dependent carbon dots are prepared, and the relationship between their chemical composition and fluorescent emission is discussed. Furthermore, potential applications of the as‐prepared carbon dots to multicolor bio‐labeling and multidimodal sensing are demonstrated.